Evaluation of Periodontal Status in Female Patients with Endometriosis: A Protocol for a Cross-sectional Study - Dolly Gabada; Priyanka Jaiswal; Amit Reche (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Periodontal medicine indicates a strong relationship between Periodontal Health (PH) or disease and ‘systemic health.’ Although Periodontal Disease (PD) is quite distant from the area affected by endometriosis, both conditions share a similar pathogenesis. Both endometriosis and PD are chronic inflammatory diseases that occur more commonly in patients with systemic disorders. Moreover, significant alterations in immune modulators have been shown to occur in both diseases. Need for the Study: The research is to evaluate the correlation between endometriosis and PH for early diagnosis, treatment planning, and prevention of long-term sequelae. Aim: To evaluate the PH status in female patients with endometriosis. Materials and Methods: A cross-sectional study will be carried out in the Department of Periodontics, Sharad Pawar Dental College and Hospital, Datta Meghe Institute of Higher Education and Research (Deemed to be University), Sawangi (M), Wardha, Maharashtra, India from September 2023 to March 2024, involving 384 participants (192 patients diagnosed with endometriosis and 192 controls). Assessment of oral hygiene, plaque accumulation, gingival status, Probing Pocket Depth (PPD), Clinical Attachment Level (CAL), Gingival Recession (GR), and other factors will be measured to evaluate the PH of the patients.